Understanding Cloud Growth Strategies: Elasticity vs. Scalability in Modern Cloud Infrastructure - Janak Bharat Bhalla (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the critical distinction between elasticity and scalability in cloud computing environments, clarifying how these often-confused concepts represent fundamentally different approaches to resource management. Elasticity focuses on immediate, automatic adjustments to resource allocation in response to real-time demand fluctuations, while scalability addresses long-term capacity planning to accommodate anticipated growth. The article examines the implementation technologies behind elastic systems, the architectural considerations necessary for scalable infrastructure, and the business implications of each approach. Through detailed comparison and case studies from e-commerce and media streaming domains, the article demonstrates how integrated strategies combining both elasticity and scalability create cloud architectures that optimize resource utilization while ensuring sustainable growth capacity, enabling organizations to maintain performance during demand spikes while minimizing costs during normal operations.